Breeding for micronutrients in staple food crops from a human nutrition perspective - Welch, Ross M.; Graham, Robin D. (Journal of experimental botany, 2004)
Over three billion people are currently micronutrient (i.e. micronutrient elements and vitamins) malnourished, resulting in egregious societal costs including learning disabilities among children, increased morbidity and mortality rates, lower worker productivity, and high healthcare costs, all factors diminishing human potential, felicity, and national economic development. Nutritional deficiencies (e.g. iron, zinc, vitamin A) account for almost two‐thirds of the childhood death worldwide. Most of those afflicted are dependent on staple crops for their sustenance. Importantly, these crops can be enriched (i.e. ‘biofortified’) with micronutrients using plant breeding and/or transgenic strategies, because micronutrient enrichment traits exist within their genomes that can to used for substantially increasing micronutrient levels in these foods without negatively impacting crop productivity. Furthermore, ‘proof of concept’ studies have been published using transgenic approaches to biofortify staple crops (e.g. high β‐carotene ‘golden rice’ grain, high ferritin‐Fe rice grain, etc). In addition, micronutrient element enrichment of seeds can increase crop yields when sowed to micronutrient‐poor soils, assuring their adoption by farmers. Bioavailability issues must be addressed when employing plant breeding and/or transgenic approaches to reduce micronutrient malnutrition. Enhancing substances (e.g. ascorbic acid, S‐containing amino acids, etc) that promote micronutrient bioavailability or decreasing antinutrient substances (e.g. phytate, polyphenolics, etc) that inhibit micronutrient bioavailability, are both options that could be pursued, but the latter approach should be used with caution. The world’s agricultural community should adopt plant breeding and other genetic technologies to improve human health, and the world’s nutrition and health communities should support these efforts. Sustainable solutions to this enormous global problem of ‘hidden hunger’ will not come without employing agricultural approaches.